2018
DOI: 10.1177/0040517518805384
|View full text |Cite
|
Sign up to set email alerts
|

A novel concept to produce periodic varied structural composite yarn via cyclical changing of the spacing between filaments and the strand

Abstract: In this study, a novel concept has been developed as a cyclical spacing-change method to produce periodic varied structural composite yarn. Geometrical analysis indicated that the cyclical change of spacing between filaments and the strand altered the yarn formation zone shapes from corefil to sirofil, causing cyclic yarn structure variations from the hairy core–sheath (corefil section) to the smooth spiral filament wrapping (sirofil section). A mechanical analysis revealed the corefil section with more twists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Comparison of blending ratios of different gradient colored yarns Segment number Blending ratios of HY1 % Blending ratios of HY2 % Blending ratios of HY3 % Blending ratios of HY4 % the test segment length of the yarn was 10 m, and 10 successive segments were tested for each type of yarn according to the Chinese textile industry-standard (CN) FZ/T 01086-2000. [21][22][23][24] A XL-2 automatic single-yarn tensile tester was applied to test the tensile properties of each type of yarn, each sample was tested 20 times, with a test speed of 500 mm/min, and the gauge length was 500 mm, with a pre-tension of 10.5 cN. [25][26][27][28]…”
Section: Performance Testing and Characterization Of Gradient Colored Yarnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of blending ratios of different gradient colored yarns Segment number Blending ratios of HY1 % Blending ratios of HY2 % Blending ratios of HY3 % Blending ratios of HY4 % the test segment length of the yarn was 10 m, and 10 successive segments were tested for each type of yarn according to the Chinese textile industry-standard (CN) FZ/T 01086-2000. [21][22][23][24] A XL-2 automatic single-yarn tensile tester was applied to test the tensile properties of each type of yarn, each sample was tested 20 times, with a test speed of 500 mm/min, and the gauge length was 500 mm, with a pre-tension of 10.5 cN. [25][26][27][28]…”
Section: Performance Testing and Characterization Of Gradient Colored Yarnsmentioning
confidence: 99%
“…The surface hairiness of different varieties of gradient colored yarns was studied in an attempt to measure differences between them. 23 The surface hairiness of the gradient colored yarns from HY1 to HY4 can be illustrated in Table 11, where the amount of surface hairiness of the 1-7 mm initially rises to a maximum and then declines. For yarn HY2, its 1 mm hairiness is the greatest, approximately 893.50, 2-7 mm hairiness is also higher, and 8 mm hairiness also possesses a certain level.…”
Section: Comparison Of Surface Hairiness Of Different Gradient Colored Yarnsmentioning
confidence: 99%
“…Instead of the eccentric device used in a previous study, 13 an electric device (Figure 3) was installed on a experimental HFX-A6 type ring frame to force filaments (guided by traversing godet wheels) to perform migrations during their inputting into the front roller nip (Figure 4), causing periodic changes in the filaments' position in the composite sirospun triangle. The migration frequency (or speed) of the godet wheels was set at 80 times/min to produce a novel composite sirospun yarn.…”
Section: Experimental Detailmentioning
confidence: 99%
“…12 This study is different from a previous study, which focuses on cyclic structural changed yarn using one multifilament and a single staple strand. 13 In particular, the influence of filament migration between siro strands on yarn structure and properties is theoretically analyzed and predicted for the novel composite siro-spinning. A verified experiment is then conducted to produce novel composite sirospun, corefil sirospun, and siro corespun yarns on a ring frame.…”
mentioning
confidence: 99%
“…A previous study reported that a strong composite yarn can be achieved when filaments are parallel with the yarn stem. 27 Therefore, a conventional corefil yarn with two buried F1 and F2 filaments is predicted to have the maximum strength. Disappointingly, excessive hairiness of corefil yarns is supposed to result in poor anti-friction.…”
Section: Property Prediction Of Different Structured Composite Yarnsmentioning
confidence: 99%